TRABALHO E RUA Análise acerca do trabalho de rua em São Luís na passagem do século XIX ao XX - CÂMARA, Paulo Roberto Pereira (2008)
Description and analysis of the street work in São Luís, Maranhão, in the historical context of the passage of the century XIX to the XX. It investigates like the desires of civility of the local elite served as justification for the implementation of measures seeking the street workers' social discipline, as well as, of other popular groups. It demonstrates as the infractions to the determinations of the Codes of Municipal Positions in what it refers in general to the use of the urban space and, specifically, to the exercise of the street workers' activities it implicated in pejorative speeches on those that did of your street work atmosphere. It still identifies some of the professional categories that took the street as stage of exercise of your occupations and that way the free workers' rent had configured as a characteristic line of the inheritance Brazilian slavery.